Textbook of dermatology - Švecová, Danka; Danilla, Tibor, 1943-; Lekárska fakulta Univerzity Komenského v Bratislave (Bratislava : Comenius University in Bratislava, 2017)
Medical students may use this book, as an introduction to dermatology, for it will stand them in good stead in pursuing their training in other specialties. Since dermatology is a highly visual specialty we have concentrated on providing detailed clinical and morphological descriptions. The book is organised in sections including aetiology and pathogenesis followed by clinical features, diagnostic properties and therapy in all discussed diagnoses. The book contains more than 400 pictures of discussed skin diseases helping the students in getting a complex vision of dermatology as well as venereology. This information will help them understand the subject. The book may help them also in their future practise in case of becoming dermatologists or any other specialists. The skin projects inner organ disorders and therefore the knowledge of skin symptoms is useful for all medical students. The therapy of discussed skin diseases contains the most advanced therapeutic modalities as well as the latest most frequently used regimens. This textbook wants to show to students that dermatology is one of the still growing specialities and the current knowledge of immunology. molecular biology and molecular genetics as well as pathophysiology show us the new scope of this subject. Many excellent dermatopathology books are available; we refer the reader to these sources for more detailed information.
Bibliogr. odkazy
Register
Keywords: dermatológia; choroby kožné infekčné -- etiológia -- diagnostika -- terapia; venerológia; choroby sexuálne prenosné -- etiológia -- diagnostika -- terapia; choroby kože a spojivového tkaniva -- etiológia -- diagnostika -- terapia; choroby vlasov; choroby nechtov; névus; nádory kože -- etiológia -- diagnostika -- terapia; učebnica